2015
DOI: 10.3758/s13423-015-0833-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-world spatial regularities affect visual working memory for objects

Abstract: Traditional memory research has focused on measuring and modeling the capacity of visual working memory for simple stimuli such as geometric shapes or colored disks. Although these studies have provided important insights, it is unclear how their findings apply to memory for more naturalistic stimuli. An important aspect of real-world scenes is that they contain a high degree of regularity: For instance, lamps appear above tables, not below them. In the present study, we tested whether such real-world spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
6
52
1
Order By: Relevance
“…Our finding thus raises the question whether the previously reported regularity effects in multi-object perception can be reduced to the effects of typical individual object location. On a behavioral level, some previous studies oppose this notion by demonstrating that the benefits of multi-object regularities cannot be explained by the relative location of the constituent objects (Kaiser et al, 2014, 2015; Stein et al, 2015). Although these results suggest that positional regularities in multi-object and single-object processing offer complementary benefits, further research is needed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our finding thus raises the question whether the previously reported regularity effects in multi-object perception can be reduced to the effects of typical individual object location. On a behavioral level, some previous studies oppose this notion by demonstrating that the benefits of multi-object regularities cannot be explained by the relative location of the constituent objects (Kaiser et al, 2014, 2015; Stein et al, 2015). Although these results suggest that positional regularities in multi-object and single-object processing offer complementary benefits, further research is needed.…”
Section: Discussionmentioning
confidence: 96%
“…Natural environments contain positional regularities on different levels, both on the levels of multiple (e.g., a lamps typically hang above tables) and individual objects (e.g., a lamp is typically in the upper visual field). Previous research has primarily focused on the latter: Recent behavioral studies have demonstrated that regularity structures in multi-object arrangement facilitate behavior in capacity-limited visual tasks (Gronau & Shachar, 2014; Kaiser et al, 2014; Kaiser, Stein, & Peelen, 2015; Stein, Kaiser, & Peelen, 2015), and neuroimaging studies demonstrated that they enable the brain to integrate information across objects that appear in frequently experienced arrangements (Baeck, Wagemans, & Op de Beeck, 2013; Kaiser & Peelen, 2018; Kaiser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both working memory and long-term memory have been shown to benefit from scene-related contextual factors, such as background information, correct spatial relations among objects, and semantic and functional relations among stimuli (Brewer & Treyens, 1981; Hollingworth, 2006; Kaiser et al, 2015; Gronau & Shachar, 2014). However, it is possible that the recruitment of such factors during search, which requires more engagement with the structural and semantic content, will cause better recall.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, familiarity or stored knowledge can also increase working memory capacity estimates (15)(16)(17)(18). Furthermore, paradigms where interference is minimized with real-world objects also show that participants can remember a very large number of objects, also without reaching a fixed capacity limit (19).…”
mentioning
confidence: 99%